(untitled) (Bangladesh Journal of Botany, 2020)
The chemical composition of seeds of Chrozophora brochiana (Vis.) Schweinf. as well as stability of the oil extracted from the seeds affected by germination have been investigated. C. brochiana seed was found to be a rich source of oil (42.9%) and protein (18.2%). Seed germination increased the moisture, protein, fiber and ash contents and decreased the fat and carbohydrate contents. The fatty acid composition was also influenced by germination where linoleic and oleic acids increased and stearic acid decreased. The concentrations of Na, K, Cu and Ca were higher in germinated seeds. FTIR spectroscopy was utilized to screen changes in the germinated and ungerminated seeds during the successive heating at 70°C for 72 hrs. It was found that the oil extracted from germinated seeds was oxidized faster than ungerminated seeds when subjected to successive heating.